1998
DOI: 10.1093/mutage/13.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Aneuploidy in male Indian muntjac cells is limited to the Y2 chromosome

Abstract: In untreated cell cultures of Indian muntjac (Munticus muntiacus vaginalis; 2n = 6 female, 7 male) we observed that spontaneous aneuploidy is limited primarily to the Y2 chromosome. We therefore treated the cells with aneugenic agents to determine if induced aneuploidy follows the same pattern and, hence, if there are limitations on the generation of aneuploidy or survival of cells lacking certain chromosomes. Exposing the cells to benomyl (8-100 micrograms/ml for 1 h), caffeine (5 x 10(-5)-2 x 10(-4) M for 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…It is noteworthy that any potential loss of a single chromosome in Indian muntjac females would represent the loss of 1/3 of the haploid genome, which would seriously compromise cell viability. In agreement, previous work reported that chromosome missegregation and aneuploidy in Indian muntjac primary fibroblasts were essentially limited to the smallest Y 2 chromosome in males [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…It is noteworthy that any potential loss of a single chromosome in Indian muntjac females would represent the loss of 1/3 of the haploid genome, which would seriously compromise cell viability. In agreement, previous work reported that chromosome missegregation and aneuploidy in Indian muntjac primary fibroblasts were essentially limited to the smallest Y 2 chromosome in males [ 47 ].…”
Section: Discussionsupporting
confidence: 90%
“…Conditions that readily induce aneuploidy in human and mouse cells only allow for loss or gain of the small sex chromosome Y2 in muntjac cells. Missegregation of the large chromosomes in muntjac is not tolerated due to gene dosage effects [27]. Most mammals must live with the occasional aneuploid cell, however, because they fully depend on spindle dynamics to detect and prevent chromosome missegregation [12,25].…”
Section: Coping With Merotelic Attachmentsmentioning
confidence: 99%
“…Another insight emerging from these recent studies [7,14] is that there does not appear to be an obvious relationship between the rates of chromosome missegregation for certain chromosomes and the severity of the corresponding aneuploidy. An earlier study in male Indian muntjac cells showed that aneuploidies for the Y chromosomes (the Indian muntjac possesses two Y chromosomes, denoted Y1 and Y2) were the only aneuploidies observed in untreated cell populations, with aneuploidy for the Y2 chromosome (the smaller of the two) being the most common [15], suggesting that cells carrying aneuploidies for any of the other, larger chromosomes are unlikely to survive. Similarly, aneuploidy for chromosome 1 is almost never observed in human miscarriages [4], hinting to the possibility that the selective pressure against such aneuploidy is so In Indian muntjac (A), centromere-kinetochore size strongly correlates with the probability of a chromosome to missegregate during mitosis.…”
Section: Current Biologymentioning
confidence: 98%